Broadband antireflective superhydrophobic self-cleaning coatings based on novel dendritic porous particles. Issue 10 (19th January 2016) - Du, Xin; Xing, Yi; Li, Xiaoyu; Huang, Hongwei; Geng, Zhi; He, Junhui; Wen, Yongqiang; Zhang, Xueji
Abstract : Novel dendritic porous particles were employed to fabricate broadband antireflective superhydrophobic self-cleaning coatings by facile dip-coating method. Abstract : Broadband antireflective (AR) superhydrophobic self-cleaning coatings were fabricated based on novel dendritic porous silica nanoparticles (HPSNs) by a facile dip-coating method. The coatings comprised a bottom AR nanoporous silica layer and a top superhydrophobic HPSNs layer. Dendritic silica particles with unique hierarchical pore structures and surface roughness not only increased the roughness of coating surface, but also did not obviously decrease the transmittance of the coated glass slide. A glass slide with the optimal coating had a maximum transmittance of 96.2% at a wavelength of 522 nm, minimum reflection of 2.3% at a wavelength of 580 nm, and excellent superhydrophobicity (WCAs: 157.8°, sliding angle: <1°). The average transmittance increased by more than 4.0% at a wavelength range of 400–1100 nm. This work provides a promising way to design and prepare a broadband AR superhydrophobic self-cleaning coating for optical devices and energy harvesting.